Superoutburst of a New Sub-Period-Minimum Dwarf Nova CSS130418 in Hercules - D. Chochol; S. Shugarov; N. Katysheva; I. Volkov; A. Zharova; E. Pavlenko; N. Pit; R. Zvagelsky; O. Antoniuk; A. Baklanov; N. Borisov; M. Gabdeev (Acta Polytechnica CTU Proceedings)
Multicolour photometry of a new dwarf nova CSS130418 in Hercules, which underwent superoutburst on April 18, 2013, allow to classified it as a WZ Sge-type dwarf nova. The phase light curves for different stages of superoutburst are presented. The early superhumps were used to determine the orbital period Porb = 64.84(1) minutes, which is shorter than the period minimum ~78 minutes for normal hydrogen-rich cataclysmic variables. We found the mean period of ordinary superhumps Psh = 65.559(1) minutes. The quiescent spectrum is rich in helium, showing double peaked emission lines of H I and He I from accretion disk, so the dwarf nova is in a late stage of stellar evolution.